Pengaruh Terapi Musik Tradisional Terhadap Tingkat Depresi Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa Di Ruang Hemodialisa Dr. Soehadi Prijonegoro Sragen - Lina Puji Astuti ((JKG) Jurnal Keperawatan Global, 2018)
Backgound. Largely, patients with chronic renal failure undergoing hemodialysis are depressed. One therapy to reduce the rate of depression is music therapy, music therapy can respond the body into relaxation and calm that can reduce levels of depression. The aim of this study is (1) Determine the level of depression in patients with chronic renal failure (2) Determine the effect of music therapy on the level of depression in patients with chronic renal failure. The research methods. This research used a pre-post test design with a one-group pre-post test data analysis used by the Wilcoxon test. Researches. There was a significant effect of music therapy on decreased levels of depression in patients with chronic renal failure undergoing hemodialysis at Dr. Soehadi Prijonegoro Hospital, Sragen. This is evidenced by the Wilcoxon test which was obtained p = 0.000. Because the value of p <0.05, so that there is the effect of music therapy on depression levels. Conclusion. There was a significant effect of music therapy on decreased levels of depression in patients with chronic renal failure undergoing hemodialysis at Dr. Soehadi Prijonegoro Hospital, Sragen